Chloroquine is a safe autophagy inhibitor for sustaining the expression of antioxidant enzymes in trophoblasts. (February 2023) - Furuta, Atsushi; Shima, Tomoko; Yoshida-Kawaguchi, Mihoko; Yamada, Kiyotaka; Yasuda, Ippei; Tsuda, Sayaka; Yamaki-Ushijima, Akemi; Yoneda, Satoshi; Higashisaka, Kazuma; Cheng, Shi-Bin; Matsumoto, Kenji; Tsutsumi, Yasuo; et al.
Abstract: Inhibition of autophagy contributes to the pathophysiology of preeclampsia. Although chloroquine (CHQ) is an autophagy inhibitor, it can reduce the occurrence of preeclampsia in women with systemic lupus erythematosus. To clarify this important clinical question, this study aimed to address the safety of CHQ in trophoblast cells from the viewpoint of homeostasis, in which the anti-oxidative stress (OS) response and autophagy are involved. We used Western blotting to evaluate the protein levels in the trophoblast cells. The expression levels of heme oxygenase-1 (HO-1), an anti-OS enzyme, mediate resistance to OS induced by hydrogen peroxide (H2 O2 ) in trophoblast cell lines. Among the autophagy modulators, bafilomycin A1 (BAF), an autophagy inhibitor, but not autophagy activators, suppressed HO-1 expression in BeWo cells; CHQ did not suppress HO-1 expression in BeWo cells. To clarify the role of autophagy in HO-1 induction, we observed no difference in HO-1 induction by H2 O2 between autophagy-normal and autophagy-deficient cells. As for the mechanism of HO-1 induction by OS, BAF suppressed HO-1 induction by downregulating the expression of neighbor of BRCA1 gene 1 (NBR1) in the selective p62-NBR1-nuclear factor erythroid 2-related factor 2 (Nrf2) autophagy pathway. CHQ did not inhibit HO-1 expression by sustaining NBR1 expression in human villous tissues compared to BAF treatment. In conclusion, CHQ is a safer medicine than BAF for sustaining NBR1, which resist against OS in trophoblasts by connecting selective autophagy and the anti-OS response. Graphical Abstract: ga1 Highlights: Syncytiotrophoblast cells constantly expressed HO-1 and were more resistant to oxidative stress than EVT cells. H2 O2 activated autophagy accompanied by HO-1 expression in some trophoblast cell lines. HO-1 induction by oxidative stress was associated with selective autophagy but not macroautophagy. Chloroquine, an autophagy inhibitor used in pregnant women with SLE, maintained HO-1 by keeping NBR1.